UTILIZATION OF AGRO-INDUSTRIAL WASTE AS ANTIOXIDANTS AND NATURAL DYES - Ribas, Jessyca Caroline Rocha; Florentino, Leandra da Silva (Seven Editora, 2026)
The generation of agro-industrial residues represents a growing environmental and economic challenge, especially within food production chains. A large portion of these residues presents high potential for valorization due to the presence of high-value bioactive compounds. In this context, the present article aimed to review the use of agro-industrial residues as sources of antioxidants and natural colorants applicable to the food industry. The methodology consisted of a review of scientific literature, analyzing studies published in recent years in national and international databases, addressing the chemical composition, extraction methods, and technological applications of these by-products. The results indicate that peels, seeds, and pomace are rich in phenolic compounds, flavonoids, carotenoids, and anthocyanins, which exhibit high antioxidant activity and coloring potential. These compounds can be used to replace synthetic additives, contributing to improved nutritional quality of foods and reduced health risks to consumers. Furthermore, the valorization of agro-industrial residues is aligned with the principles of the circular economy, promoting sustainability and added value to by-products. It is concluded that the use of these residues is a promising alternative; however, further research is required regarding the stability, safety, and industrial feasibility of these applications.DOI: https://doi.org/10.56238/sevened2026.001-038